2007
DOI: 10.1186/1745-6215-8-18
|View full text |Cite
|
Sign up to set email alerts
|

Telecare motivational interviewing for diabetes patient education and support: a randomised controlled trial based in primary care comparing nurse and peer supporter delivery

Abstract: Background: There is increasing interest in developing peer-led and 'expert patient'-type interventions, particularly to meet the support and informational needs of those with long term conditions, leading to improved clinical outcomes, and pressure relief on mainstream health services. There is also increasing interest in telephone support, due to its greater accessibility and potential availability than face to face provided support. The evidence base for peer telephone interventions is relatively weak, alth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 13 publications
0
9
0
3
Order By: Relevance
“…Two randomized trials have suggested improved self efficacy and HbA1c from peer-led self management support within Spanish-speaking communities [24] and increased physical activity from peer support amongst African-American women [25]. Other trials have been conducted in Dublin (evaluating group support in primary care, including an educational component) [26,27], Warwick (evaluating telecare by peers) [28] and Michigan (comparing peer support with nurse care management) [20]. …”
Section: Introductionmentioning
confidence: 99%
“…Two randomized trials have suggested improved self efficacy and HbA1c from peer-led self management support within Spanish-speaking communities [24] and increased physical activity from peer support amongst African-American women [25]. Other trials have been conducted in Dublin (evaluating group support in primary care, including an educational component) [26,27], Warwick (evaluating telecare by peers) [28] and Michigan (comparing peer support with nurse care management) [20]. …”
Section: Introductionmentioning
confidence: 99%
“…For instance, Dale and colleagues [24-25] trained peer supporters to deliver a 6-session, telephone-based, self-management support intervention designed to enhance routine clinic visits. The goal of the intervention was to motivate patients to implement treatment recommendations made by health care providers during clinic visits.…”
Section: Introductionmentioning
confidence: 99%
“…The self-management materials were supplemented with three coaching sessions and carers reported a functional improvement in the people they were caring for and this was associated with reductions in expressed emotion and accommodating and enabling behaviours (Goddard et al, 2011 ). Moreover, in ED treatment generally, the addition of guidance improves the effectiveness of self-help (Grover et al, 2011a , 2011b ) and there are promising results in other health-related fields for trained peer support delivered by telephone (Dale, Caramlau, Docherty, Sturt, & Hearnshaw, 2007 ; Ghorob et al, 2011 ; Goldman, Ghorob, Eyre, & Bodenheimer, 2013 ; McCusker et al, 2012 ). However, as yet, neither professionals nor carers' skills have been measured in terms of fidelity to the intervention or guidance being offered.…”
Section: Introductionmentioning
confidence: 99%